Evaluation of Quality of Life in Patients with Chronic Renal Failure (Journal of Hama University, 2020)
The quality of life for patients with chronic renal insufficiency, whose condition requires continuous hemodialysis, is greatly affected, as this effect is associated with changes in their daily habits and lifestyle with physical, psychological and environmental dimensions. Therefore, the present descriptive study aimed to assess the quality of life of 30 patients in the Department of artificial kidney in Tishreen University Hospital, selected by the convenient sample method, and data were collected using a tool developed by the researcher based on the quality of life scale developed by WHO. The results showed that the highest percentage of patients was an average overall level of quality of life, the level of physical health was poor, moderate in psychological, and weak in the environment dimension. The study recommended to provide psychological counseling periodically to patients, and provide support in decision-making, encourage them to adapt to the disease, provide appropriate solutions, to conduct educational sessions for patients about the nature of their disease and ways to live with it, and conduct research on factors affecting the quality of life of patients with renal insufficiency.